PERBANDINGAN METODE PEMBELAJARAN PREVIEW QUESTION READ REFLECT RECITE REVIEW (PQ4R) DENGAN DIRECTED READING THINKING ACTIVITY (DRTA) DALAM KETERAMPILAN MEMBACA PEMAHAMAN SISWA - Aini, Kurrata; Munirah; Bahri, Aliem (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Research to find out how students' reading comprehension skills through the PQ4R learning method, how students' reading comprehension skills through the DRTA learning method, whether there are differences between the PQ4R method and the DRTA method in students' reading comprehension skills. Using a quantitative approach with quasy experimental design type nonequivalent multiple-group research. The population of this study was all grade V students of Elementary School cluster 1 Wolo District, Kolaka Regency which amounted to 304 students. The sample of this study used cluster random sampling technique based on population needs. Data analysis is done through descriptive statistical analysis. The prerequisite tests used are normality tests and homogeneity tests then hypothesis tests (Independent Sample T Test). The results showed that there were differences in the application of the PQ4R learning method and the DRTA learning method to students' reading comprehension skills. The score obtained from the independent sample t test is 0.001 which shows smaller than 0.05. Keywords: DRTA, PQ4R, reading comprehension skills